Uniform Flow of Micro-Polar fluid Past a Permeable Sphere Saturated With Viscous Fluid (Journal of Namibian Studies : History Politics Culture, 2023)
The investigativestudy of continuousflow of micro-polar fluid past a spherical porous ballsaturated with viscous fluidis considered. The velocity field within as well as outside the sphere is referred in terms of stream function. The flow pattern is obtained under regularity condition at infinity and normal velocity continuity on the sphere's surface. The formula for Drag acting on the sphere is derived and the results of physical parameters like porosity parameter and micro-polarity parameter on the flow and on the Dragon the sphere are presented in the form of diagrams.